Ragam Bahasa Indonesia di Media Sosial - Satrya Wibisana Mirza (CV. Alim's Publishing, 2023)
Indonesian is the official language of our country, Indonesia. Indonesian as the main community communication element and tool in Indonesia. The development of information technology allows global communication so fast that it means it can reach across countries and across continents. In this discussion